119k views
1 vote
Select the correct answer. Factor the expression. A. (7x − 4)(7x − 4) B. (4x − 7)(4x − 7) C. (7x + 4)(7x − 4) D. (4x + 7)(4x − 7)

1 Answer

5 votes

Answer:

C. (7x + 4)(7x − 4)

Explanation:

Given expression:

49x² - 16

Using difference of two squares:

A² - B² = (A + B)(A - B)

49x² - 16 = (7x)² - (4)²

= (7x + 4)(7x - 4)

C. (7x + 4)(7x − 4)

Check:

(7x + 4)(7x − 4)

Open parenthesis

= 49x² - 28x + 28x - 16

= 49x² - 16

Select the correct answer. Factor the expression. A. (7x − 4)(7x − 4) B. (4x − 7)(4x-example-1
User Theremin
by
4.4k points